PENGEMBANGAN MEDIA EVALUASI BERBASIS APLIKASI EXCEL TO WHATSAPP - Prakoso, Firza Agung; Rochmawati, Rochmawati (Jurnal Pendidikan Ilmu Sosial, 2020)
The research aims to 1) develop an e-learning evaluation media based on the Excel to WhatsApp application. 2) Testing the feasibility of evaluation media developed by experts. 3) Testing the feasibility of the media based on the responses of class X students in basic banking subjects at SMK N 1 Probolinggo. This development refers to the 4D model by Thiagarajan which includes the stages of define, design, develop, and disseminate. The results of the review and expert validation in this study indicate that the feasibility of the media, the feasibility of evaluation, and the feasibility of the material get an average of 88% with the criteria of "very feasible" where the data is processed qualitatively with a Likert scale. The results of the questionnaire response of students obtained an average of 94% with the criteria "very feasible" where the data was processed quantitatively with the Guttman scale. Therefore, this Excel to WhatsApp based evaluation media is suitable for use as a support for learning activities.